2020
DOI: 10.1016/j.arthro.2019.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factor Delivery to a Cartilage-Cartilage Interface Using Platelet-Rich Concentrates on a Hyaluronic Acid Scaffold

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In simpler terms, immunogenicity refers to the ability of a substance to initiate a cell-mediated immune response. To date, there is limited research on the role of platelet concentrates as non-autogenous biological additives 35,36 . Our experiment examined the synergetic effect of L-PRF on the proliferation of non-autogenous SCs.…”
Section: Discussionmentioning
confidence: 99%
“…In simpler terms, immunogenicity refers to the ability of a substance to initiate a cell-mediated immune response. To date, there is limited research on the role of platelet concentrates as non-autogenous biological additives 35,36 . Our experiment examined the synergetic effect of L-PRF on the proliferation of non-autogenous SCs.…”
Section: Discussionmentioning
confidence: 99%
“…Combinations of HA with glucocorticoid or platelet-rich plasma has been used in the treatment of OA. Titan et al [ 40 ] used platelet-rich concentrate in combination with HA in bovine cartilage to enhance cartilage injury repair. Smith et al [ 41 ] reported that the intraarticular injection comprising corticosteroid and HA exhibited better pain relief than that obtained by injecting only HA.…”
Section: Discussionmentioning
confidence: 99%
“…In the article "Growth Factor Delivery to a Bovine Cartilage Defect Using Leukocyte-Rich Platelet-Rich Concentrates on a Hyaluronic Acid Scaffold," Titan, Schär, Hutchinson, Demange, Chen, and Rodeo 4 have performed a well-executed, high-quality in vitro investigation to assess whether human leukocyte-rich tissue platelet-rich plasma (L-PRP) or platelet-rich fibrin (L-PRF) delivered on a hyaluronic acid (HA) scaffold would improve tissue formation in a bovine chondral defect model. They found that both the HA scaffold combined with L-PRP and the HA scaffold combined with L-PRF showed greater biomechanical durability in vitro than the HA scaffold alone.…”
Section: See Related Article On Page 1431mentioning
confidence: 99%
“…As with many in vitro studies evaluating the effect of PRP on cartilage, 5 the translatability of the results of Titan et al 4 may be limited by several factors: the small size of the lesions, use of several human blood donors, lack of a biomechanical evaluation of axial compressive or horizontal shearing forces, and more. Nevertheless, this study is unique in terms of the rigorous methodology used, and its outcomes suggest that HA scaffolds augmented with L-PRP or L-PRF may play a role in Tel Aviv, Israel (R.G.)…”
Section: See Related Article On Page 1431mentioning
confidence: 99%
See 1 more Smart Citation